2008
DOI: 10.1097/01.ccm.0000300083.74726.43
|View full text |Cite
|
Sign up to set email alerts
|

Persistent villi hypoperfusion explains intramucosal acidosis in sheep endotoxemia*

Abstract: In this model of endotoxemia, fluid resuscitation corrected both serosal intestinal and sublingual microcirculation but was unable to restore intestinal mucosal perfusion. Intramucosal acidosis might be due to persistent villi hypoperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 55 publications
6
87
1
2
Order By: Relevance
“…Dubin et al [69] showed that fluid resuscitation was able to normalize systemic and splanchnic perfusion, as well as intestinal serosal microvascular blood flow but not ileal villi blood flow, which may explain the persistence of intramucosal acidosis in endotoxemic sheep after fluid resuscitation.…”
Section: Effects Of Iah On Tissue Perfusion and Microcirculationmentioning
confidence: 99%
“…Dubin et al [69] showed that fluid resuscitation was able to normalize systemic and splanchnic perfusion, as well as intestinal serosal microvascular blood flow but not ileal villi blood flow, which may explain the persistence of intramucosal acidosis in endotoxemic sheep after fluid resuscitation.…”
Section: Effects Of Iah On Tissue Perfusion and Microcirculationmentioning
confidence: 99%
“…Villi hypoperfusion, however, remained present. (12) Accordingly, Boerma et al showed a dissimilar behavior of sublingual and gut microcirculation in postoperative septic patients with intestinal ostomies. Consequently, different microcirculatory beds could behave differently.…”
Section: Editorialmentioning
confidence: 99%
“…Several measurements can be obtained from these images (24) , including functional capillary density (density of perfused capillaries), total vessel density, and a semi-quantitative estimation of the flow patterns. Although semi-quantitative, these scores have a good reproducibility for flow estimation through different sites (12)(13)(14)(25)(26)(27) , with good agreement of flow measurements with software in experimental conditions (28) , even though the analysis may sometimes be more complex in the gut (29) . Some software for image analysis are currently available, but the technical procedure is somewhat still semiautomatic and allows only measurements of flows lower than 1 mm/sec.…”
Section: How To Evaluate Microcirculation At the Bedsidementioning
confidence: 99%